2006
DOI: 10.1017/s002211200600036x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the wall shear stresses during the progressive enlargement of symmetric abdominal aortic aneurysms

Abstract: International audienceThe changes in the evolution of the spatial and temporal distribution of the wall shear stresses (WSS) and gradients of wall shear stresses (GWSS) at different stages of the enlargement of an abdominal aortic aneurysm (AAA) are important in understanding the aetiology and progression of this vascular disease since they affect the wall structural integrity, primarily via the changes induced on the shape, functions and metabolism of the endothelial cells. Particle image velocimetry (PIV) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 63 publications
(49 reference statements)
10
88
0
1
Order By: Relevance
“…This description of the flow phenomena in pulsatile flow through a Gaussian shaped model aneurysm agrees very well with what was found in experiments by Salsac et al (2006). These authors also observed that the vortex motions within the dilatation induce strong spatial and temporal variations of the wall shear stress, especially near the distal end.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This description of the flow phenomena in pulsatile flow through a Gaussian shaped model aneurysm agrees very well with what was found in experiments by Salsac et al (2006). These authors also observed that the vortex motions within the dilatation induce strong spatial and temporal variations of the wall shear stress, especially near the distal end.…”
Section: Discussionsupporting
confidence: 89%
“…Again, this agrees with what was found by us. Our computational approach allowed us to investigate a somewhat larger range of parameter values than Salsac et al (2006). Our results support the conclusion of Salsac et al (2006) that longer aneurysms are less pathological than short ones.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations